Targeting Misconduct in Prison by Modifying Occupational Factors in Correctional Facilities - Vogel, Joanna; Sauter, Julia; Vogel, Bob-Oliver; Dahle, Klaus-Peter (Frontiers in Psychiatry, 2020)
Misconduct in prison is a phenomenon, which by its nature is hard to observe. Little is known about its origins and its modifiability. This study presents data on the level of misconduct in prison perceived by staff members and examines its impact on occupational factors. Data from officers, which also included i.e. team climate, job satisfaction, self-efficacy and sick days, was collected at three different correctional units in Berlin, Germany (N = 60). The study reveals higher rates of perceived misconduct in prison on regular units as compared to treatment units within the observed facilities. In addition, regression analysis provides evidence for an association of rates of misconduct in prison, sick days and low self-efficacy. Results are discussed in terms of providing a model that supports the idea of a network entailing occupational factors and misconduct in prison and which can be utilized to target misconduct in prison with suitable interventions.